Tramadol — the Impact of its Pharmacokinetic and Pharmacodynamic Properties on the Clinical Management of Pain - Klotz, Ulrich (Arzneimittelforschung, 2003)
Tramadol (CAS 36282-47-0) plays an important role in the management of pain. With its dual mechanism of action (opioid agonist; weak noradrenaline and serotonin reuptake inhibitor) tramadol provides a kind of combined/adjuvant pain therapy. Besides its proven clinical efficacy tramadol is a safe drug as respiratory depression, cardiovascular side effects, drug abuse and dependence are of minor clinical relevance, unlike some other opioids.Following oral administration the bioavailability of tramadol is high (70−90 %) and with new slow release preparations twice daily administration enables effective pain control. Tramadol is characterised by low plasma protein binding (20 %) and quite extensive tissue distribution (apparent volume of distribution about 3 l/kg). Elimination is primarily by the hepatic route (metabolism by CYP2D6 to an active metabolite and by CYP3A4 and CYP2B6) and partly by the renal route (up to 30 % of dose). Elimination half-lives of the active agents range between 4.5 and 9.5 h and total plasma clearance of tramadol is moderately high (600 ml/min).The interaction potential of tramadol is neglectable, as it does not affect the disposition of other drugs. It should be taken into account that inducers (e.g. carbamazepine) or inhibitors (e.g. quinidine for CY2D6) of drug metabolism might modify the elimination of tramadol. Like-wise, if kidney (creatinine clearance below 30 ml/min) or hepatic function is severely impaired, some dosage reduction (approximately by 50 %) or extension of the dosage interval should be considered.In conclusion, tramadol is an effective and safe analgesic with a very low interaction potential. Therefore it represents a drug of first choice if moderate to severe pain states have to be treated in pediatric, adult and elderly patients including those with poor cardiopulmonary function.
Keywords: CAS 36282-47-0; Opioid, synthetic; Tramadol, comorbidity, drug interactions, pain, pharmacodynamics, pharmacokinetics